Sejarah Kemunculan dan Konsep Pemikiran Aliran Murjiah Serta Pengaruhnya Pada Masyarakat Islam Zaman Sekarang - Muhamad Parhan; Amanda Sephira Nuraini; Azahra Harianti; Dara Salsabila Rahman; Indra Hadi Kurniawan; Muhammad Alviazha Qinthara (STIKes Ibnu Sina Ajibarang, 2024)
This article will discuss the kalam sect in Islam. The dispute that occurred during Ali bin Abi Talib's caliphate was the beginning of the emergence of various understandings, which resulted in the division of Muslims into several groups at that time. Like the Khawarij, who have the opinion that those who judge other than Allah's law are infidels, those who commit major sins are also punished as infidels. There are also Shiites, who, according to some opinions that emerged after the Tahkim incident, are a group that supports Ali's opposition rather than the Khawarij. Even the Shiites are very fanatical about the Ahlul Bait. Between the two, there is a neutral group that does not side with the Khawarij and Shiites, namely the Murjiah. Therefore, the author wants to examine the concept of the Kalam school of thought, especially the Murjiah, and its history so that it can become a new perspective that provides insight to purify Islamic teachings. The research method uses qualitative methods, which we took from various sources, articles, and journals.